A NEED ANALYSIS ON ENGLISH FOR LOCAL TOUR GUIDES AT TARO TOURISM VILLAGE IN GIANYAR REGENCY BALI - Ni Luh Putu Sri Widhiastuty; I Ketut Murdana (JURNAL KEPARIWISATAAN, 2023)
The research aimed to identify, describe, and analyze the English language requirements for local tour guides at Taro Tourism Village in Gianyar Regency, Bali, as they carry out their daily responsibilities, including greetings, welcomes, introductions, and providing information. A qualitative research approach was employed, utilizing non-probability sampling techniques such as purposive sampling, snowball sampling, and abundant sampling. Data collection tools included non-participation observation checklists, questionnaires, and structured interview questions. The study's findings were based on two data analysis methods: Present Situation Analysis (PSA) and Target Situation Analysis (TSA). The PSA revealed that 35% of respondents and critical informants possessed a basic proficiency in general English, sufficient for guiding tourists at Taro Tourism Village. However, TSA indicated that 65% of respondents and critical informants required English for Specific Purposes (ESP), focusing on integrated language skills (speaking, listening, reading, and writing) and specialized vocabulary related to local tourist attractions, arts, cultures, traditions, and more. In summary, the research highlighted the need for local tour guides in Taro Tourism Village to enhance their English language skills, particularly in the context of ESP, to effectively communicate with tourists and provide an enriching experience while showcasing the village's attractions and culture.